The Dignity and God’s Image in Every Human Being (Gen 1: 26-27): Challenges for Human Dignity in Africa (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article titled: “The Dignity and God’s image in Every Human Being (Gen 1: 26-27): Challenges for Human Dignity in Africa” articulates that man/woman was created in the image of God. It is the quality attained in the course of creation. The image of God (imago Dei) in human being stands for the attributes of God in man which gives mankind a special dignity and status. The divine image in man points to the existential abilities to commune and fellowship with God, while dignity is the transferred unique and supreme moral worth of God, His very nature and resemblance as expressed in man/woman. Unfortunately, this privilege is taken for granted and abused in the contemporary African society. More often than not, we hear that the dignity of the human person were trampled upon via physical abuse, torture, disgrace, cruel punishment, inhuman treatment, assault, castigation, terror, harassment, murder, emotional trauma and humiliation of people. Instances abound all over Africa especially in Nigeria, Ghana, Kenya, South Africa, Cameroun, Niger, etc., where Christians seeking for healing and restoration were forced to eat grass; mercilessly flogged to cast out demons and some had to swallow snake. Essentially, this paper argues and upholds the dignity and rights of human person and denounces what is essentially inhuman. Using descriptive and analytical methods, the paper underscores that the scholars, especially the biblical scholars, must courageously affirm that this dignity should be understood, maintained and presented in Africa, so that the dignity and God’s image in every human being could be respected.